International volunteerism and urethral stricture disease: a review - Frankel, Jason K.; Murphy, Gregory P. (Translational Andrology and Urology; Vol 7, No 4 (August 15, 2018): Translational Andrology and Urology (Male Genitourinary Reconstruction and Trauma), 2018)
Global health is an ever-expanding area of interest for many healthcare workers around the world. In recent years, it has become apparent that much of the global disease burden is surgical. Urologic disease is no exception—many international organizations send volunteers around the world to support Urologic services in countries that lack capacity and resources. Urethral stricture represents a unique opportunity for specialized surgical management that vastly improves long term morbidity. Here we review the prevalence, etiology, and management of urethral stricture from a global perspective while highlighting impact of international urologic volunteer efforts.